Legal Aspects of the Right to Nationality Pursuant to Myanmar Citizenship Law - Su Yin Htun (Journal of Southeast Asian Human Rights, 2019)
It is universally accepted that everyone has the right to citizenship. Myanmar’s framework on the right to nationality constitutes a unique, exclusive, ethnic citizenship system based on jus sanguinis or the law of blood. Myanmar’s Citizenship Law was enacted in 1982 by repealing the Union Citizenship Act of 1948. As citizenship parameters were changed by the Law, many people in the Kachin, Karen, and Rakhine states lost their nationality rights and consequently suffered human rights abuses. In the Rakhine state, serious communal violence occurred in 2012, 2016, and 2017, and the government declared a state of emergency. This research paper focuses on how Myanmar can adhere to international standards for nationality rights. It provides a historical overview and legal analysis of citizenship laws in Myanmar using a human rights lens and offers suggestions for legal reforms that can help address the problem of statelessness in Myanmar. Specifically, it recommends the use of the jus soli, or the law of the soil, approach to citizenship.